Development of lung and muscle protein factories to deliver therapeutic monoclonal antibodies - Antepowicz, A; Tan, A; Pringle, A; Hyde, S; Gill, D (Mary Ann Liebert Inc, 2016)
Recombinant therapeutic proteins, of which monoclonal antibodies (mAbs) represent the largest market, are used to treat diseases including cancer, blood and immune disorders. The cost and complexity of large-scale production and purification of mAbs translates to high cost of therapy. We hypothesise that our rSIV.F/HN lentiviral lung gene delivery platform, currently undergoing preclinical evaluation for cystic fibrosis gene therapy, could be used to establish protein factories within patients' lungs.